Standardized Definitions of In Utero Human Immunodeficiency Virus and Antiretroviral Drug Exposure Among Children . (23rd November 2021) - Slogrove, Amy L; Burmen, Barbara; Davies, Mary Ann; Edmonds, Andrew; Abrams, Elaine J; Chadwick, Ellen G; Goetghebuer, Tessa; Mofenson, Lynne M; Paul, Mary E; Thorne, Claire; Williams, Paige L; Vicari, Marissa; et al.
Abstract: In countries with high human immunodeficiency virus (HIV) prevalence, up to 30% of pregnant women are living with HIV, with fetal exposure to both HIV and antiretroviral therapy during pregnancy. In addition, pregnant women without HIV but at high risk of HIV acquisition are increasingly receiving HIV preexposure antiretroviral prophylaxis (PrEP). Investments are being made to establish and follow cohorts of children to evaluate the long-term effects of in utero HIV and antiretroviral exposure. Agreement on a key set of definitions for relevant exposures and outcomes is important both for interpreting individual study results and for comparisons across cohorts. Harmonized definitions of in utero HIV and antiretroviral drug (maternal treatment or PrEP) exposure will also facilitate improved classification of these exposures in future observational studies and clinical trials. The proposed definitions offer a uniform approach to facilitate the consistent description and estimation of effects of HIV and antiretroviral exposures on key child health outcomes. Abstract : In countries with high human immunodeficiency virus (HIV) prevalence, 20%–30% of pregnant women have HIV and receive antiretrovirals. Proposed definitions offer a uniform approach to describing/estimating the effects of in utero HIV and antiretroviral exposure on child health outcomes.